Restoration interventions produce opposite and non‐additive benefits on tree establishment in degraded forest clearings. Issue 4 (20th September 2021) - Rivas Rivas, Maximino B.; Douterlungne, David; Gómez Aparicio, Lorena; Badano, Ernesto I.; Flores Cano, Jorge Alberto
Abstract : The natural regeneration of forests is declining in human‐modified landscapes and overcoming ecological barriers to the seedling establishment is paramount to its restoration. This study focus on two common forest regeneration barriers: excessive sun exposure and low‐quality soils. A degraded clearing with eroded and compacted soils within a disturbed oak forest in Mexico was chosen, and 20 experimental plots in a randomized factorial block design were set up to test seedling performance in the artificial shade and in forest topsoil that was transferred from a nearby remnant forest, as well as a combination of both. We sowed 400 acorns from two oak species ( Quercus eduardii and Q. viminea ) and monitored the emerging seedlings for 63 months. Our results confirm different survival and growth rates between species, ontogenetic stages, and environmental micro‐conditions. The effect of artificial shade on seedling performance was positive in weathered soil but negative or neutral in transferred forest soil. Restoration interventions did not have additive benefits; seedling performance was improved by both restoration interventions applied separately though was not further enhanced when both actions were combined. Both species had different mechanisms to cope with water stress, which resulted in different photosynthetic rates under full sun. Trade‐offs resulted in different life stages that were more enhanced by different restoration strategies; survival and growth were most enhanced by applying artificial shade or transferring forest topsoil, respectively. Restoration practitioners may prioritize seedling survival in harsh conditions and growth in less severe degraded sites or apply interventions sequentially over time.